The Use of Power Ultrasound in Mining - Gaete-Garreton, L (Elsevier Inc., 2014)
This chapter deals with the application of power ultrasound in the mining industry. The uses of power ultrasound are addressed in three aspects: (1) determination of the stress state of rock mass for safety reasons and to plan mining work; (2) ultrasound with mineral grinding, for energy efficiency and wear improvement; and (3) the uses of power ultrasound in the mineral concentration process (flotation). © 2015 Elsevier Ltd. All rights reserved.